Students’ Vocabulary Learning through Augmented Reality (AR): EFL Student Teachers’ Perceptions: Persepsi Calon Guru Bahasa Inggris terhadap Pembelajaran Kosa Kata melalui Augmented Reality (AR) - Fika Megawati; Shanina Sharatol Ahmad Shah; Rahmania Sri Untari; Sheila Agustina; Chandrika Rahmania Cahyani (Academia Open, 2023)
This study explores the integration of Augmented Reality (AR) into English language education, focusing on the topic of professions. Student teachers in a Micro Teaching class were invited to assess the AR-based learning activities designed to aid vocabulary comprehension. Questionnaires were distributed to gather perceptions on the potential usefulness and suitability of the AR product for classroom use. The results affirm that AR holds great promise in enlivening and enriching English language lessons, as student teachers provided numerous creative ideas for its implementation. Valuable recommendations for product improvement were also obtained. As English teachers strive to develop effective teaching media, they should consider how such technology facilitates meaningful learning objectives. This research offers insights into the positive impact of AR in language education and highlights its implications for improving students' language proficiency in specific domains. Highlights: AR integration in English learning: Augmented Reality (AR) offers an innovative approach to enhance English vocabulary learning in the context of professions, fostering greater engagement and interactive classroom experiences. Perceptions of student teachers: The study gathers valuable insights from student teachers' perceptions, highlighting their ideas and suggestions for effectively implementing AR-based learning activities in language classrooms. Implications for language education: The research underscores the potential of AR as a teaching tool, emphasizing its positive impact on language proficiency and the importance of meaningful content to facilitate effective learning outcomes. Keywords: Augmented Reality (AR), English Vocabulary, Profession, Student Teachers, Learning Activities